Political marketing in the 2019 Canadian federal election - Gillies, Jamie; Raynauld, Vincent 1982-; Turcotte, André (Palgrave Macmillan, 2021)
This book explores the 2019 Canadian Federal Election through a political marketing framework. Justin Trudeau's leadership appeal, coupled with the differentiation of Canadian politics from American politics over recent elections, has contributed to a spike in interest for politics in the Canadian context. This collection provides in-depth quantitative and qualitative research of different aspects of this election, including the attempted re-branding of the Conservative Party under Andrew Scheer, the marketing of the NDP with the selection of the first visible minority party leader in Canadian history, the political marketing of the Bloc Québécois, Green Party, and People's Party and, foremost perhaps, the brand maintenance of Trudeau and the Liberal Party of Canada. The book also looks at campaign marketing, and considers how the parties in this election utilized market intelligence, consumer data and vote targeting, and wedge issues during the campaign. Jamie Gillies is Associate Professor of Communications and Public Policy and Executive Director of the Frank McKenna Centre for Communications and Public Policy at St. Thomas University in Fredericton, Canada. Vincent Raynauld is Assistant Professor in the Department of Communication Studies at Emerson College in Boston, USA, Research Associate in the Groupe de recherche en communication politique (GRCP) at Université Laval in Québec, Canada, and Affiliate Professor in the Département de Lettres et Communication Sociale at the Université du Québec à Trois-Rivières, Canada. André Turcotte is Associate Professor in the School of Journalism and Communication and in the Riddell Program in Political Management at Carleton University in Ottawa, Canada
1 Introduction: The 2019 Canadian Federal Election (Vincent Raynauld, André Turcotte and Jamie Gillies) -- 2 The New (Old) Trudeau in 2019: The Challenges and Potential for Branding Prime Ministers in Government (Jennifer Lees-Marshment) -- 3 Andrew Scheer and the post-Harper Conservative Party: Materialist, Post-Materialist and Negative Branding (Kenneth Cosgrove) -- 4 Gliding In On a Wing and a Prayer: Jagmeet Singh and the NDP (James McLean) -- 5 The Bloc is Back!: The Resurgence of the Bloc Québécois in 2019 (Guy Lachapelle) -- 6 The Populist Impact: The People's Party and the Green Party (Jamie Gillies) -- 7 Go Knock Doors: 'New' Dimensions in Market Intelligence (David Coletto) -- 8 Voters as Consumers of Durable Goods (André Turcotte and Michal Moore) -- 9 Divide Et Impera: Wedge Politics in the 2019 Canadian Federal Election (André Turcotte and Vincent Raynauld) -- 10 Conclusion: Déjà Vu All Over Again? (André Turcotte, Jamie Gillies and Vincent Raynauld)
Keywords: Geschichte 2019; Elections; Marketing; Political leadership; Political communication; Politikmarketing; Wahl; Kanada